Using an aqueous two‐phase polymer‐salt system to rapidly concentrate viruses for improving the detection limit of the lateral‐flow immunoassay. Issue 12 (25th August 2014) - Jue, Erik; Yamanishi, Cameron D.; Chiu, Ricky Y.T.; Wu, Benjamin M.; Kamei, Daniel T.
ABSTRACT The development of point‐of‐need (PON) diagnostics for viruses has the potential to prevent pandemics and protects against biological warfare threats. Here we discuss the approach of using aqueous two‐phase systems (ATPSs) to concentrate biomolecules prior to the lateral‐flow immunoassay (LFA) for improved viral detection. In this paper, we developed a rapid PON detection assay as an extension to our previous proof‐of‐concept studies which used a micellar ATPS. We present our investigation of a more rapid polymer‐salt ATPS that can drastically improve the assay time, and show that the phase containing the concentrated biomolecule can be extracted prior to macroscopic phase separation equilibrium without affecting the measured biomolecule concentration in that phase. We could therefore significantly decrease the time of the diagnostic assay with an early extraction time of just 30 min. Using this rapid ATPS, the model virus bacteriophage M13 was concentrated between approximately 2 and 10‐fold by altering the volume ratio between the two phases. As the extracted virus‐rich phase contained a high salt concentration which destabilized the colloidal gold indicator used in LFA, we decorated the gold nanoprobes with polyethylene glycol (PEG) to provide steric stabilization, and used these nanoprobes to demonstrate a 10‐fold improvement in the LFA detection limit. Lastly, a MATLAB script was used to quantify the LFA results with and without the pre‐concentration step. This approach of combining a rapid ATPS with LFA has great potential for PON applications, especially as greater concentration‐fold improvements can be achieved by further varying the volume ratio. Biotechnol. Bioeng. 2014;111: 2499–2507. © 2014 Wiley Periodicals, Inc.